High Liquidity Creation and Systemic Risk in the U.S. Banking Sector - Yasar, Sara (My University, 2016)
This study focuses on bank liquidity creation as a comprehensive measure of all bank’s on and off balance sheet activities, and it specially formulates and tests the hypothesis which address the issue as to whether high total bank liquidity creation has a positive effect on systemic risk. Using a sample of large US commercial banks from 2000 to 2014, this study finds that there is a positive association between liquidity creation and systemic risk. After the Berger and Bouwman’s (2009) preferred liquidity creation is decomposed into its two main components, the results suggest that on balance sheet liquidity creation has no significant effect on the level of systemic risk, while off balance sheet liquidity creation strongly positively contributes to systemic risk. These results demonstrate that off balance sheet liquidity creation is the main component for explaining the cross-sectional variation in the level of systemic risk. The empirical findings also indicate that liquidity creation, especially its off balance component, has a stronger positive effect on systemic risk during the financial crisis in 2008.
Keywords: Liquidity creation; systemic risk; financial crisis; bank risk-taking; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|